Partisipasi Masyarakat Dalam Penerapan Konsep Sustainable Development Terhadap Pembangunan Ibu Kota Negara Nusantara - M, Mulyadi; Almagfira, Anisa; Nasution, Amanda Cherlyta Apriliani; Fatimah, Ghefira Nur; Wahdah, Azzhara Nikita; Ramadhon, Daffa Charisma Putra; Alvito, Haykal Rizki; Kamil, Surya Insani; Tambunan, Joy Catherine Carina; A, Annisa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The relocation of the National Capital is a national strategic project to create a sustainable city that attracts investment from both within the country and abroad. Public participation is community involvement in the decision-making process and policy determination. This research uses quantitative research methods whose focus is collecting scientific data and references to answer the problem formulation in the introduction. From this research, the results obtained are (1) Community participation is important in every phase of development, implementation, impact evaluation and conceptualization to ensure success; (2) The government's steps in ensuring the participation of the Indonesian people in the concept of sustainable development in developing IKN can use the SDGs pillars.